1999
DOI: 10.1046/j.1365-2699.1999.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale spatial variation of pasture molluscan faunas within a relic watermeadow system at Wylye, Wiltshire, U.K.

Abstract: Summary Aim To acquire general quantitative data on the molluscan faunas of floodplain pastures, assessing the influence of (minor) topographic variation on molluscan distribution. Additionally, to examine the potential for analogous comparison with fossil data Location The study was located within a relic watermeadow system currently used as floodplain pasture near Wylye, Wiltshire, U.K. Methods Mollusca were extracted from forty turf samples collected from relic carriers (cf. ridges) and relic drains (cf.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Ondina et al (2004) reported high moisture requirements for several species (e.g., Cochlicopa lubrica, Vertigo pygmaea and Perpolita hammonis) which were present in our plots, mainly from the upland fringes and upland (Table 3). Moisture is welldocumented as an important factor influencing the composition of grassland snail communities (Davies & Grimes 1999;Martin & Sommer 2004a;Hettenbergerová et al 2013). Secondly, a low calcium content of upland grasslands is not suitable for the presence of steppe species and is suboptimal even for common species of open habitats (Table 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Ondina et al (2004) reported high moisture requirements for several species (e.g., Cochlicopa lubrica, Vertigo pygmaea and Perpolita hammonis) which were present in our plots, mainly from the upland fringes and upland (Table 3). Moisture is welldocumented as an important factor influencing the composition of grassland snail communities (Davies & Grimes 1999;Martin & Sommer 2004a;Hettenbergerová et al 2013). Secondly, a low calcium content of upland grasslands is not suitable for the presence of steppe species and is suboptimal even for common species of open habitats (Table 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Although land snails do not appear to be dependent on the presence of particular plant species, they are very dependent on the structure of their habitat (Boycott, 1934; Grime & Blythe, 1969; Cameron & Morgan‐Huws, 1975; Labaune & Magnin, 2001) and have a low dispersal ability. Little is known on these themes for the Mediterranean area, although related research has been undertaken on the impact of grazing on lowland snails in Britain (Cameron & Morgan‐Huws, 1975; Cameron, 1978; Ruesink, 1995; Davies & Grimes, 1999). A second, subsidiary goal was to acquire quantitative data on the land snail communities of dry pastures to enable detection of ‘pastoral signatures’ from Holocene assemblages in the same geographical area.…”
Section: Introductionmentioning
confidence: 99%
“…First, buried land surfaces from beneath long barrows or other Neolithic monuments should be subject to a spatially orientated molluscan sampling programme. The only such programme undertaken to date (Whittle et al 1993) clearly indicated a wood/scrub-grassland edge setting at least in one direction, and recent modern studies have confirmed how spatially restricted Mollusca can be (Davies 1999;Davies and Grimes 1999). Woodland may not have been as far off as was once imagined, at least at the construction stage.…”
Section: Discussionmentioning
confidence: 96%